Penentuan Calon Penerima Beasiswa Menggunakan Metode Fuzzy Tsukamoto - Rachmawati, Fitria (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
Scholarships is appreciation which are given to individuals to continue a higher level education. Scholaship is financial assistance which are given to individuals or students for different education achieved. This program is expected to alleviate the burden of students in learning certain problems costs. Fuzzy Tsukamoto’s logic is one method that can build a system to select student who can get the scholarship. The selected based on parent’s data, number of parents and the average value of each student. The results using the Fuzzy Tsukamoto method analyzed is based on 31 student data obtained error value as big as number 17.4 where can concluded the error value is relatively small